2017
DOI: 10.1016/j.ijpharm.2016.11.050
|View full text |Cite
|
Sign up to set email alerts
|

Nanoprecipitated catestatin released from pharmacologically active microcarriers (PAMs) exerts pro-survival effects on MSC

Abstract: Catestatin (CST), a fragment of Chromogranin-A, exerts angiogenic, arteriogenic, vasculogenic and cardioprotective effects. CST is a very promising agent for revascularization purposes, in "NO-OPTION" patients. However, peptides have a very short half-life after administration and must be conveniently protected. Fibronectin-coated 30 pharmacologically active microcarriers (FN-PAM), are biodegradable and biocompatible polymeric microspheres that can convey mesenchymal stem cell (MSCs) and therapeutic proteins d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Furthermore, a study with fibronectin-coated pharmacologically active microcarriers (FN-PAM) examined whether the incorporation of CST into FN-PAM and its release affects the survival of mesenchymal stem cells (MSCs) under hypoxia-generated stress conditions. It was found that this controlled release of CST limited hypoxic MSC death and enhanced cell survival in the post-hypoxic environment [ 74 ]. Hence, it appears that effective CST delivery may be a potent approach for repairing the damage caused by prolonged hypoxia.…”
Section: Chromogranin a Derivative: Catestatinmentioning
confidence: 99%
“…Furthermore, a study with fibronectin-coated pharmacologically active microcarriers (FN-PAM) examined whether the incorporation of CST into FN-PAM and its release affects the survival of mesenchymal stem cells (MSCs) under hypoxia-generated stress conditions. It was found that this controlled release of CST limited hypoxic MSC death and enhanced cell survival in the post-hypoxic environment [ 74 ]. Hence, it appears that effective CST delivery may be a potent approach for repairing the damage caused by prolonged hypoxia.…”
Section: Chromogranin a Derivative: Catestatinmentioning
confidence: 99%
“…As Hypoxia/Reoxygenation (H/R) we considered cell survival studied after exposition to DMEM-2% FBS with 3% O 2 and 5% CO 2 for 72-h and a subsequent reoxygenation (21% O 2 and 5% CO 2 ) for 3-h [39][40][41][42]. H/R protocol was obtained in an hypoxic chamber (INVIVO2 200, Belsar, Varese, Italy).…”
Section: Study Of Protection Against Oxidative Stress and Study Of Intracellular Mechanisms Of Cgrp Protection Against Hypoxia/reoxygenatmentioning
confidence: 99%
“…At the end of experiments cell survival was assessed using the cell viability test 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) kit. The plates were read by a spectrophotomer at 570 nm to obtain values of optical density [39]. All values were normalized to mean value of input control cells and expressed as percentage.…”
Section: Cell Survival Assessmentmentioning
confidence: 99%